2016
DOI: 10.1007/s12041-016-0635-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of T-1131C APOA5 and ALOX5AP SG13S114 with the susceptibility of ischaemic stroke in Morocco

Abstract: Ischaemic stroke is a multifactorial disease. Genetic polymorphisms involved in lipid, inflammatory and thrombotic metabolisms play an important role in the development of ischaemic stroke. The present study aimed to assess the relationship between T1131C APOA5 and SG13S114 ALOX5AP polymorphisms and the risk of ischemic stroke in 175 cases and 201 controls. Genotyping was performed by high resolution melting and polymerase chain reaction restriction fragment length polymorphism methods. In the case of T-1131C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Imaging (magnetic resonance imaging/computerized tomography) examination of the brain to support the clinical diagnosis was conducted in all studies. The distribution of genotypes in the controls of all studies was in agreement with HWE except for the studies by Cheng et al, Zhao et al, Xu et al, and Diakite et al21,26,29,37 Table 1 displays the study characteristics for the identified studies.…”
Section: Resultssupporting
confidence: 54%
“…Imaging (magnetic resonance imaging/computerized tomography) examination of the brain to support the clinical diagnosis was conducted in all studies. The distribution of genotypes in the controls of all studies was in agreement with HWE except for the studies by Cheng et al, Zhao et al, Xu et al, and Diakite et al21,26,29,37 Table 1 displays the study characteristics for the identified studies.…”
Section: Resultssupporting
confidence: 54%
“…Recent data revealed that a few protein genetic polymorphisms were significantly association with the risk for stroke [2224]. Here, we investigated that ApoA5, LPL, CETP and LDLR gene polymorphisms in IS patients from Xinjiang region.…”
Section: Discussionmentioning
confidence: 96%
“…Studies included in the present critical review of the literature have revealed several risk factors associated with cerebral ischemia in the local populations of interest. Indeed, high blood pressure (HBP), diabetes, smoking and heart disease were the four main risk factors listed and are as follows: HBP was reported in ( n = 20) studies (31 to 65.4%) [13, 15, 17, 18, 20, 21, 23, 25–28, 30, 33, 35–38, 40–42], diabetes in ( n = 20) studies (12–41.8%) [13, 15, 17, 18, 20, 21, 23, 25–28, 30, 33, 35–38, 40–42], cardiac diseases in 14 studies (7–44.3%) [13, 15, 17, 20, 21, 23, 25–28, 30, 33, 35, 42], atrial fibrillation as associated heart disease was specified in 9 studies (2,5–22%), and smoking in ( n = 19) studies (4–41.8%) [13, 15, 17, 18, 20, 21, 23, 25–28, 30, 33, 35, 37, 38, 40–42].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these risk factors, other risk factors have been reported such as dyslipidemia in ( n = 16) studies (0–61.8%) [13, 15, 17, 18, 20, 23, 25–28, 30, 33, 35–37, 42], obesity in ( n = 6) studies (10.7–26.1%) [13, 17, 18, 26, 30, 35], the notion of a previous stroke was noted in ( n = 10) hospital series (5–26.6%) [13, 15, 23, 25–28, 30, 32, 35], alcoholism in ( n = 10) studies [13, 15, 20, 25, 32, 33, 35, 38, 40, 41], oral contraception in ( n = 3) studies (6.6–12.2%) [30, 32, 33], and migraine in a single study at 6.5% [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation